1993
DOI: 10.1007/bf00381151
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic studies in lymphocytes of workers exposed to 2,3,7,8-TCDD

Abstract: Chromosome aberrations and sister chromatid exchanges (SCEs) were evaluated in 27 workers with current 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) blood lipid concentrations exceeding 40 parts per trillion (ppt) and in 28 unexposed referents of similar age. No statistical differences were found between the two groups in the percentages of gaps, chromatid or chromosome exchanges, chromatid or chromosome breaks/fragments/deletions, multiple aberrations, or the overall percentage of aberrations including gaps (1.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Descriptive accounts of the signs and symptoms experienced after exposure have been reported as well as laboratory studies correlating biomonitoring data with clinical chemistries, immunological variables, and cytogenetic outcomes; mortality follow up studies; and most recently a long term morbidity study based on medical insurance data have been reported.7 [11][12][13][14] These investigations identified 115 cases of chloracne (56 classified as severe) in a cohort of 254 people." Most cases were diagnosed during the early clean up period and no severe cases were found after 1959.…”
Section: Study Backgroundmentioning
confidence: 99%
“…Descriptive accounts of the signs and symptoms experienced after exposure have been reported as well as laboratory studies correlating biomonitoring data with clinical chemistries, immunological variables, and cytogenetic outcomes; mortality follow up studies; and most recently a long term morbidity study based on medical insurance data have been reported.7 [11][12][13][14] These investigations identified 115 cases of chloracne (56 classified as severe) in a cohort of 254 people." Most cases were diagnosed during the early clean up period and no severe cases were found after 1959.…”
Section: Study Backgroundmentioning
confidence: 99%
“…In rats, DNA strand breaks were found in vivo in liver and peritoneal lavage cells after TCDD exposure (IARC 1997). In humans, no chromosomal aberrations and SCE were found in 27 workers with TCDD blood lipid concentrations exceeding 40 pg after accidental exposure (Zober et al 1993). Also, no significant difference was observed in the mean SCE rates between ''Yusho'' patients approximately 27 years after the outbreak of the Yusho accident and the general Japanese population (Nagayama et al 2001).…”
Section: Introductionmentioning
confidence: 97%
“…It is an accepted paradigm that SCEs arise during the period of lymphocyte culture, which would suggest that the veterans have a persistent clastogen still in their bloodstream, or that they possess a common instability. Dioxin, a contaminant of Agent Orange, is known to be an inducer of SCEs (Zober et al, 1993). It is also very persistent and has an average half-life in humans of 7.78 years (Geyer et al, 2002), which suggests that New Zealand Vietnam veterans who were exposed to defoliants more than 30 years ago are still very likely to have elevated dioxin levels when compared to non-veterans.…”
Section: Resultsmentioning
confidence: 99%
“…The above statement endorses numerous studies where this assay has been used successfully as a bioindicator linking chemical exposure with possible genetic damage (Zober et al, 1993;Garaj-Vrhovac and Zeljezic, 2001;Arias, 2003; Abstract. From July 1965 until November 1971, New Zealand Defence Force Personnel fought in the Vietnam War.…”
mentioning
confidence: 99%